Corticolous Lichen Diversity on Trees in Urban and Suburban Settings in New Amsterdam, Berbice, Guyana - Bacchus , Bebe Raazia; Silva , Phillip N. B. Da (Advanced Research in Biological Science Vol. 1, 2023)
Given the dearth of information on corticolous lichens in urban and suburban locations in Guyana, this study was conducted to identify, document and compare corticolous lichen diversity on the barks of trees in urban and suburban environments in New Amsterdam, Guyana. Within each of four study sites a 50m by 20m plot was delineated and healthy mature trees were sampled for the presence of corticolous lichens. Forty-one healthy trees from five species were studied using (10cm by 50cm) ladder quadrats on the tree trunk (N, S, E, W) at 150cm height. This study recorded 14978 individual lichens belonging to 10 families, 13 genera and 18 species. Species richness, evenness and diversity of corticolous lichens communities were determined and Shannon Diversity Index, Simpson’s Diversity Index, Pielou’s Index, Menhinick’s Index and Whittaker’s diversity index were used as the basis for comparing lichen diversity. The results revealed that the urban sites studied were more diverse and had a higher species richness and species evenness than the suburban sites. The overall diversity (0.8902) of New Amsterdam was indicative of a very diverse lichen community. Pairwise comparison of Whittaker’s beta diversity index for all four sites was 0.5. Menhinick’s Index for richness for New Amsterdam was 0.1471. Cladonia parasitica, Hypotrachyna laevigata and Usnea cornuta were restricted to Swietenia mahagoni trunks and Dirinaria applanate was restricted to Cocos nucifera. Corticolous lichen diversity appeared to have been influenced by the diversity of host trees since the species richness of corticolous lichens decreased as host tree specificity decreased.